2020
DOI: 10.1111/jcmm.15106
|View full text |Cite
|
Sign up to set email alerts
|

Oridonin inhibits the migration and epithelial‐to‐mesenchymal transition of small cell lung cancer cells by suppressing FAK‐ERK1/2 signalling pathway

Abstract: Small cell lung cancer (SCLC) is a severe malignant with high morbidity; however, few effective and secure therapeutic strategy is used in current clinical practice. Oridonin is a small molecule from the traditional Chinese herb Rabdosia rubescens. This study mainly aimed to investigate the role of oridonin on inhibiting the process of H1688, a kind of small cell lung cancer cells from human. Oridonin could suppress H1688 cell proliferation and induce their apoptosis in a high dosage treatment (20 μmol/L).Mean… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
37
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 47 publications
(38 citation statements)
references
References 35 publications
1
37
0
Order By: Relevance
“…As documented in literature, utilization of oridonin increased the level of E-cadherin and ALP, reduced the vimentin, phospho-FAK levels, snail, slug, and LDH in human small cell lung cancer cell line H1688 with concentration of 2.5, 5, 10, 20, and 40 µM for 24 and 48 h in vitro. Of course, the author also confirmed the antilung cancer effect of oridonin in the model of BALB/c nude mice (Xu et al, 2020). Another study on the anti-lung cancer of oridonin proved that, oridonin sensitized cisplatin-induced apoptosis via AMPK/Akt/mTOR-dependent autophagosome accumulation in A549 Cells (Yang et al, 2019a).…”
Section: Anticancer Activitymentioning
confidence: 73%
See 1 more Smart Citation
“…As documented in literature, utilization of oridonin increased the level of E-cadherin and ALP, reduced the vimentin, phospho-FAK levels, snail, slug, and LDH in human small cell lung cancer cell line H1688 with concentration of 2.5, 5, 10, 20, and 40 µM for 24 and 48 h in vitro. Of course, the author also confirmed the antilung cancer effect of oridonin in the model of BALB/c nude mice (Xu et al, 2020). Another study on the anti-lung cancer of oridonin proved that, oridonin sensitized cisplatin-induced apoptosis via AMPK/Akt/mTOR-dependent autophagosome accumulation in A549 Cells (Yang et al, 2019a).…”
Section: Anticancer Activitymentioning
confidence: 73%
“…However, several lines of evidence indicated that oridonin may exhibit adverse effects, even toxicity under specific circumstances, which sparked intense debate and concern about security of oridonin. As discussed above, it was discovered that oridonin showed antitumor activity on small cell lung cancer (SCLC), but at the same time, HE staining revealed a certain degree of cytotoxicity in hepatic tissue after treatment with oridonin (10 mg/kg) ( Xu et al, 2020 ). In addition, intervention of oridonin induced abnormalities in zebrafish, such as uninflated swim bladder and pericardial congestion at an EC 50 of 411.94 mg/L in vitro , as well as it also decreased the body length of zebrafish.…”
Section: Toxicitymentioning
confidence: 99%
“…CIS is one of the first-line choices chemotherapeutic drugs for esophageal squamous cell carcinoma (ESCC), which shows the promising effect; however, it is a cell cycle nonspecific drug, has no clear target tissue and poses several adverse effects. On the other hand, ORI, a major diterpenoid component of leaf extracts from Rabdosia rubescens, has been demonstrated to be effective to a number of cancers [ 17 ], such as esophagus [ 18 ], leukemia [ 19 ], lung [ 20 ], pancreatic [ 21 ], prostate [ 22 ], breast [ 23 ] and colon[ 24 ] both in vivo / in vitro . In the current study, we report for the first time a synergistic antitumor effect of CIS and ORI on human ESCC cells, the main finding is that using CIS plus ORI has a selective synergistically effect to p53-mutant ESCC.…”
Section: Discussionmentioning
confidence: 99%
“…It has the ability to inhibit the proliferation of H1688 cells and induce their apoptosis under high-dose treatment (20 μ mol/L). At the same time, oridonin (5 and 10 μ mol/L) inhibits the FAK-ERK1/2 signaling pathway without affecting cell proliferation and apoptosis [ 69 ].…”
Section: Metastasis and Inhibition Of Tumor Invasionmentioning
confidence: 99%